Does body weight support improve neural and biomechanical measures during treadmill gait in children with unilateral cerebral palsy? - Banerjee, Rajit; Kim, Yushin; Bulea, Thomas C.; Damiano, Diane L. (Frontiers in Rehabilitation Sciences, 2025)
IntroductionBody weight support (BWS) treadmill training, commonly utilized to improve gait, has inconsistent evidence of effectiveness across disorders.MethodsWe aimed to comprehensively evaluate its scientific rationale by comparing immediate effects of two weight support levels (20%, 40%) to unsupported (0%) treadmill walking on neural and biomechanical measures in children with unilateral cerebral palsy (CP) and typical development (TD). We hypothesized BWS would demonstrate positive effects only in CP. Participants included 10 with TD and 8 with CP (mean age = 14.6 and 15.4 years, respectively).ResultsMinimal or no group differences or BWS effects were found for synergy number, structure or Walk-DMC, whereas the Gait Deviation Index (GDI) showed a significant interaction with 20% BWS where the dominant side in CP improved with 20% BWS while both sides in TD worsened. Beta band EEG activation from 0% to 20% BWS showed a significant triple interaction increasing in the non-dominant and decreasing in the dominant hemisphere in TD, while increasing in both in CP. A worsening trend was seen with 40% BWS in all measures except z scores.ConclusionBWS has beneficial effects on kinematics in CP supporting the basic premise for use in neurorehabilitation at the body structure level.